Geografia-monstro: um currículo assombroso nos anos iniciais do ensino fundamental - Maira Freitas de Araujo (2017)
Geography presents itself as a compulsory subject in the curriculum of the initial years of Elementary School. However, it evidences many disputes to be present in this stage of schooling, competing with other knowledges that are generally preferred to it. This dissertation investigates, based on the post-critical perspective, the geography curriculum of three classes of the initial three years of Elementary School,in a municipal school of Belo Horizonte. The objective is to show how the geography curriculum is configured in the school, placing a focus on established power relations and the discourses that are prioritized in the teaching of this discipline in the first three years of elementary school. Methodologically, a bricolage was performed between elements of ethnography and the analysis of Foucaultian-inspired discourse. The argument put forward here is that the geography curriculum of the three groups investigated is a monstrous curriculum because, at the same time as it provokes fears, uncertainties, insecurities, difficulties in its demarcation, it also causes uneasiness that allows border crossings, discoveries, creations, joys, productions of knowledge. It is a curriculum that haunts, provoking terror and enchantment. To develop this argument, I show in this dissertation how this curriculum is hybrid, since it is composed of the knowledge of the school geography, of the knowledge of the children, of the teachers and of other disciplines that now compete for space, sometimes articulate to produce the curriculum Geography of thegroups investigated. Moreover, in this curriculum, power relations are established between the knowledge of school geography and the knowledge of religious discourse. These relationships do not always take the form of a dispute, but they also form alliances between apparently immiscible knowledges. This monstrous curriculum, in addition, allows the juxtaposition of several spaces, so that the childrenare in the classroom, but they refer to other spaces. Thus, there are heterotopias in the curriculum investigated that configure other possible, other astonishment, other geographies, which not only frighten but also create and rejoice.